2009
DOI: 10.1093/protein/gzp007
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an ultra-stable affinity reagent based on Top7

Abstract: Antibodies are widely used for diagnostic and therapeutic applications because of their sensitive and specific recognition of a wide range of targets; however, their application is limited by their structural complexity. More demanding applications require greater stability than can be achieved by immunoglobulin-based reagents. Highly stable, protein-based affinity reagents are being investigated for this role with the goal of identifying a suitable scaffold that can attain specificity and sensitivity similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…Chemical and thermal unfolding measurements showed that the engineered protein maintains stability at neutral pH, with no significant change in the free energy of unfolding when compared to native Top7. Of most relevance, ELISA experiments revealed that the engineered Top7 binds to CD4 whereas the native protein does not [11]. These findings demonstrated that Top7 displays considerable potential as an affinity reagent scaffold where binding sites for targets of interest can be grafted.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Chemical and thermal unfolding measurements showed that the engineered protein maintains stability at neutral pH, with no significant change in the free energy of unfolding when compared to native Top7. Of most relevance, ELISA experiments revealed that the engineered Top7 binds to CD4 whereas the native protein does not [11]. These findings demonstrated that Top7 displays considerable potential as an affinity reagent scaffold where binding sites for targets of interest can be grafted.…”
Section: Introductionmentioning
confidence: 93%
“…The Top7 K39E K40E K55E (referred to here as Top7) and Top7 CB1 proteins were expressed and purified as previously described [11]. Proteins were buffer exchanged (HiTrap Desalting column, GE Healthcare) into phosphate buffered saline (PBS, 100 mM NaH 2 PO 4 and150 mM NaCl) at pH 7.0 or pH 2.0.…”
Section: Circular Dichroism (Cd) Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations